Optimalisasi Pendidikan Insklusi Di SMK Muhammadiyah 1 Wates - Imam Mars Miasya Ibnu Ivan; Dinda Azzahra; Difa'ul Husna (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
Learning activities that take place with guidance, teaching and training aim to prepare children to play a role in their diverse world in the future. Learning activities that are able to achieve educational goals are certainly supported by existing components in learning such as facilities, human resources, procedures and learning equipment. In order for Islamic Education to run according to the process towards the goal of education for children with special needs (ABK), of course teachers must adhere to various PAI teaching principles, these principles include entertaining, fun, fast processing, and encouraging students to achieve achievements (Dr. Nuraini, M.S.I. 2023). Children with Special Needs have the same rights as ordinary children in receiving educational services. The provision of educational services to children with special needs must of course be the same as for children in general. This provides an idea for inclusive schools to have standard characteristics and learning models in providing services. Children with special needs are grouped into several types including: Blind, Speech Impaired, Deaf, Autism and so on. Children with special needs certainly need schools with relevant characters and learning models, so there are three learning characteristics that must be met in educational institutions, including flexible learning, non-discriminatory learning including active, cooperative and relevant learning, and the last is learning. which provides support for recognition and appreciation of the differences that each individual has. This research uses qualitative methods by collecting various information from several literacy sources. This writing is intended to describe the characteristics and learning models in inclusive schools, specifically at SMK Muhammadiyah 1 Wates.